Alternativas de rehabilitación mediante la evaluación de la infraestructura vial en carreteras de montaña - Lalangui Yaguana, Ana Carolina; Serrano Sarango, Gloria Elizabeth (Machala; Universidad Técnica de Machala, 2024)
The deficiencies that occur in the road infrastructure are related to the lack of maintenance on the roads. For this analysis, a methodology is presented based on the conditions found on the E585 road, which connects the Portovelo Canton with the El Pindo sector. To address this study, the following parameters were first evaluated, such as the pavement condition index (PCI), laboratory tests, analysis of vehicular traffic, and determination of pavement roughness (IRI). With an evaluation of each parameter, scales were used to determine what type of maintenance is necessary to apply to the road when deterioration occurs in the pavement. This type of study makes it easier for us to make decisions to be able to guide ourselves through the HDM-4 program. With the use of the software we can generate the appropriate alternatives regarding the results obtained in the methodology. In this way, the information of the criteria. that evaluates, thus performs the execution. In this way, a feasible and favorable project management will be achieved for the conservation of routine and periodic maintenance. The data obtained with the Software refers to the benefit-cost relationship, estimating the IRR and NPV. Through this, it will be possible to have a road in optimal conditions and provide good road service to users
Las deficiencias que se presentan en la infraestructura vial se relacionan por la falta de mantenimientos en las vías. Para este análisis se presenta una metodología basada en las condiciones que se encuentra la vía E585, que une el Cantón Portovelo con el sector El Pindo. Para abordar este estudio primero se evaluó los siguientes parámetros como es el índice de condición del pavimento (PCI), ensayos en el laboratorio, análisis del tráfico vehicular, determinación de la rugosidad del pavimento (IRI). Con una valoración de cada parámetro se empleó escalas para determinar qué tipo de mantenimiento es necesario aplicar en la vía cuando se presentan deterioros en el pavimento. Este tipo de estudio nos facilita la toma de decisiones para poder orientarnos mediante el programa HDM-4, con el uso del software podemos generar las alternativas debidas en cuanto a los resultados obtenidos en la metodología de esta manera se podrá completar la información de los criterios que evalúa, así realizar la ejecución. De esta forma se logrará una gestión de proyecto factible y favorable para la conservación de mantenimientos rutinarios y periódicos, los datos obtenidos con el Software hacen referencia a la relación beneficio-costo, estimando el TIR y VAN. Atreves de ello se podrá tener una vía en óptimas condiciones y dar un buen servicio de vialidad a los usuarios
Keywords: CARRETERA DE MONTAÑA; EVALUACION VIAL; ESTRUCTURA VIAL; HDM-4